A estrutura arbórea na investigação sobre borda florestal da Mata do Araldo, Porto Rico, PR, Brasil. - Almeida, Cristina Guilherme de (2013)
Mata do Araldo is a disturbed remnant of riparian formation of semideciduous forest, situated on a stretch of the Upper Paraná River floodplain (PIARP) on the left bank of the Paraná River. Several floristic inventories and Phytosociological addressing the structure and dynamics of communities and populations, as well as sustainable use of forest species, were performed in this remnant. These studies indicated the occurrence of new species of vascular plants for PIARP as well as endangered species, reinforcing the importance of conservation and further study of this remnant forest as FES representative in a riparian area of the region. The first approach of this study aimed to deepen knowledge about the structure and floristic composition of Araldo of the forest, in order to expand the sampling area. It carried out a phytosociological survey, by the method of plots, including the margin, the interior and the edge of the forest fragment. About half of the raised species were grouped into five families, highlighting Leguminosae with 13 species and Myrtaceae with seven. The floristic richness approached the values obtained in the previous phytosociological surveys, however, six families, 10 genera and 10 species were exclusive occurrence of the current survey, with seven of these species were new records. Even with the expansion of the sample area of the present study, cultratus Lonchocarpus and Tabernaemontana catharinensis remained dominant as the VI. The purpose of the second approach of this study was to investigate possible variations in structure and floristic composition of the tree community in relation to the distance from the edge of the forest fragment. To this end, it carried out a phytosociological survey; Correspondence Analysis (DCA) resulted in the separation of two groups: Border and indoor / edge. The analysis of variance showed a significant difference between these two. The results did not characterize the existence of a core area and, with the exception of marginal area, subject to greater influence of the river, the rest of the remaining behaves as a edge.